Pancreatic Protein Tyrosine Phosphatase 1B Deficiency Exacerbates Acute Pancreatitis in Mice - Bettaieb, Ahmed; Koike, Shinichiro; Chahed, Samah; Bachaalany, Santana; Griffey, Stephen; Sastre, Juan; Haj, Fawaz G. (The American journal of pathology, 2016)
Acute pancreatitis (AP) is a common and devastating gastrointestinal disorder that causes significant morbidity. The disease starts as local inflammation in the pancreas that may progress to systemic inflammation and complications. Protein tyrosine phosphatase 1B (PTP1B) is implicated in inflammatory signaling, but its significance in AP remains unclear. To investigate whether PTP1B may have a role in AP, we used pancreas PTP1B knockout (panc-PTP1B KO) mice and determined the effects of pancreatic PTP1B deficiency on cerulein- and arginine-induced acute pancreatitis. We report that PTP1B protein expression was increased in the early phase of AP in mice and rats. In addition, histological analyses of pancreas samples revealed enhanced features of AP in cerulein-treated panc-PTP1B KO mice compared with controls. Moreover, cerulein- and arginine-induced serum amylase and lipase were significantly higher in panc-PTP1B KO mice compared with controls. Similarly, pancreatic mRNA and serum concentrations of the inflammatory cytokines IL-1B, IL-6, and tumor necrosis factor-α were increased in panc-PTP1B KO mice compared with controls. Furthermore, panc-PTP1B KO mice exhibited enhanced cerulein- and arginine-induced NF-κB inflammatory response accompanied with increased mitogen-activated protein kinases activation and elevated endoplasmic reticulum stress. Notably, these effects were recapitulated in acinar cells treated with a pharmacological inhibitor of PTP1B. These findings reveal a novel role for pancreatic PTP1B in cerulein- and arginine-induced acute pancreatitis.